The Analysis of Improving the Arabic Writing Competency through Calligraphy Learning at Junior Hight School Darul Huda East Java - Ahmad Aziz Fuadi; Junaedi (Journal of Arabic Language Studies and Teaching, 2022)
In this article, the authors discuss the complex analysis of Arabic Writing Competence through Calligraphy Learning at Darul Huda Junior high school Ponorogo. The problem at students' Junior high school level is how to write Arabic properly and correctly; Arabic writing skill is presented to students with writing skills. One way to increase students' writing is by learning calligraphy. The purpose of the study was to determine the calligraphy learning process and the problems of learning calligraphy to improve students' writing. The research method uses a qualitative descriptive approach. The data sources consist of students' writing in calligraphy and calligraphy teachers. The study results show that: 1. The selection of learning methods is very urgent to achieve learning objectives, 2. The selection of calligraphy material texts must be simple and easy to understand so students can easily copy them.